2019
DOI: 10.1103/physrevb.99.195109
|View full text |Cite
|
Sign up to set email alerts
|

Charge density wave in a doped Kondo chain

Abstract: We report the existence of the charge density wave (CDW) in the ground state of 1D Kondo lattice model at the filling of n=0.75 in the weak coupling region. The CDW is driven by the effective Coulomb repulsion mediated by the localized spins. Based on our numerical results using the density matrix renormalization group method, we show that the CDW phase appears in the paramagnetic region previously known as the Tomonaga-Luttinger liquid. The emergence of this phase serves as an example of CDW phase induced wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, in some other CDW systems where the condition of the FS nesting is not well satisfied, e.g., in some transition metal dichalcogenides, other CDW mechanisms have been proposed, such as excitonic interaction [5,6], Jahn-Teller effect [7,8], momentumdependent EPC [9], and strong electron correlation [10], which are still hotly debated. CDW can also occur in strongly correlated Kondo lattice systems [11,12], but how the CDW ordering interacts with the many-body Kondo effect remains largely unexplored. Theoretically, the many-body Kondo screening [13,14] requires mobile conduction electrons near E F , while the CDW order normally reduces the DOS near E F via gap opening.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some other CDW systems where the condition of the FS nesting is not well satisfied, e.g., in some transition metal dichalcogenides, other CDW mechanisms have been proposed, such as excitonic interaction [5,6], Jahn-Teller effect [7,8], momentumdependent EPC [9], and strong electron correlation [10], which are still hotly debated. CDW can also occur in strongly correlated Kondo lattice systems [11,12], but how the CDW ordering interacts with the many-body Kondo effect remains largely unexplored. Theoretically, the many-body Kondo screening [13,14] requires mobile conduction electrons near E F , while the CDW order normally reduces the DOS near E F via gap opening.…”
Section: Introductionmentioning
confidence: 99%
“…The spincharge interplay brings about the possibility of spontaneous formation of the CDW, without relying on repulsive Coulomb interactions or electron-phonon interactions 33 . Indeed, it was shown that a CDW appears in the Kondo lattice model in one 34 , two 35 , and infinite dimensions 36,37 . Similar instability was also discussed for the periodic Anderson model 38,39 .…”
Section: Introductionmentioning
confidence: 99%
“…At small J the Kondo effect is suppressed and the phase belongs to a universal class of Tomonaga-Luttinger liquid at generic fillings with zero charge and spin gap 21,22 . However, for certain J at the commensurate fillings of n = 1 2 23 , n = 3 4 24 , and n = 1 25 the state becomes insulating, and the insulating state at the quarter filling (n = 1…”
Section: Introductionmentioning
confidence: 99%